Prototype Aplikasi Real Count Pemilihan Kepada Daerah Pada Badan Pengawas Pemilihan Umum Kota Palembang - Zaini, Kurniawan; Maryani, Maryani; Suhartini, Suhartini (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
PILKADA (Regional Head Election) and its deputy are routine activities carried out by each region to carry out democratic government activities. The Provincial KPU carries out Pilkada, and Regency / City KPU is collectively responsible for implementing general elections, supervised by the Provincial Bawaslu and Regency / City Bawaslu. The Palembang City Bawaslu's task in the vote counting process is to oversee the movement of recapitulation data from the TPS Supervisor level, Village / Sub-district Supervisors (PKD), and District Election Supervisory Committee (Panwascam) to the City Bawaslu so that there is no vote inflation which is considered dishonest and unfair. The process of collecting C1 and C-Plano form data to be recapitulated from the lower level to the upper level at the Palembang City Bawaslu collected, the process will take a relatively long time if done manually, especially limited by the long distance and poor natural conditions. In line with the development of increasingly modern technology, considering the need for data and the need for rapid dissemination of information on Pilkada results, in this study, the author will design Real Counting (also known as parallel vote aggregation) as a helpful way to monitor and accelerate the vote aggregation process in the form of an application prototype. This study aims to provide a prototype design for the Pilkada real count application at Bawaslu Palembang City. The software development method used in this study is the waterfall model method, which consists of analysis, design, coding, testing, and support or maintenance.